Safe movement of food and forage crops germplasm: ICARDA’s experience in the Arab region - Kumari, Safaa; Moukahel, Abdulrahman; El Miziani, Inaam (The Arab Society for Plant Protection, 2022)
Germplasm exchange for research and breeding purposes is essential for crop improvement in the face of climate change and population growth. To contribute towards achieving sustainable development goals, the germplasm exchange need to accelerated to keep up with a world-changing food demand at an ever-increasing pace. However, the movement of living materials is not without the risk of inadvertent movement of associated organisms, including pests. Therefore, extreme care is required to ensure that exchanged germplasm is pest-free. The Consortium of International Agricultural Research Centers (CGIAR) is a global partnership that unites international organizations engaged in research about food security. CGIAR centers have established Germplasm health units (GHUs) to ensure the safety of exchanged plant materials, and compliance with the FAO International Plant Protection Convention (IPPC) procedures and the International Standards for Phytosanitary Measures (ISPMs) used by National Plant Protection Organizations (NPPOs) to prevent the introduction and control the spread of pests along with plants or plant products. Within the framework of the CGIAR, ICARDA has the world mandate for the improvement of barley, lentil and faba bean. It also has a regional mandate for the improvement of wheat (bread and durum), Kabuli chickpea and pasture and forage crops in the dry areas, including the Arab region. The development of improved germplasm and elite genotypes for use by national, regional and international breeding programs is the major objective of the ICARDA crop improvement program. In order to safeguard countries from quarantine risks (insect pests, pathogens and weeds) associated with the movement of germplasm, ICARDA follows a regulatory and quarantine program working in close collaboration with competent institutions where ICARDA has platforms for crop breeding, germplasm multiplication and evaluation and genetic resources exchange in Lebanon and Morocco. ICARDA’s GHU is responsible for the monitoring, clearance and documentation of safe germplasm movement at the center, to do so, all incoming and outgoing genetic resources and breeding germplasm must go through a strict quarantine monitoring system (seed health testing, quarantine clearance based on national and international procedures and rules). Annually, ICARDA’s GHU tests more than 100,000 exchanged seed samples from ICARDA mandate crops to be distrusted for more than 70 countries, including Arab region. The center is fully equipped with a seed science and technology and data management staff, in addition to the necessary crop management and post-harvest seed operation facilities. The seed production process is monitored by an independent GHU in coordination with the quarantine systems of the host countries in which ICARDA operates. The role of ICARDA’s GHU in the safe exchange of germplasm in the Arab region will be presented.